Advancing Social Justice Through an Interdisciplinary Approach to Clinical Legal Education: The Case of Legal Assistance of Windsor - Rose Voyvodic; Mary Medcalf (Washington University Journal of Law & Policy, 2004)
Since its inception in 1974, the University of Windsor’s Clinical Law Program at Legal Assistance of Windsor (LAW) has placed law students in a downtown community legal clinic staffed by lawyers and social workers. As an interdisciplinary clinical legal education program whose mission is “to provide access to justice to the poor,” LAW holds numerous possibilities for advancing a social justice agenda in both professional education and practice. In this Essay, however, we suggest that its success in this regard depends upon renewed and purposeful attention to certain critical factors: (1) a shared understanding of LAW’s goals and values; (2) curriculum design that is reflective of these goals and values; and (3) institutional sanction and support for the goals and values.
Keywords: Interdisciplinary approach in education; Clinical legal education; Social justice